Re-excision after unplanned excision of soft tissue sarcomas: Long-term results. (September 2020) - Scoccianti, Guido; Innocenti, Matteo; Frenos, Filippo; Muratori, Francesco; Sacchetti, Federico; Beltrami, Giovanni; Capanna, Rodolfo; Campanacci, Domenico Andrea
Abstract: Background: Unplanned excisions of soft tissue sarcomas are still not infrequent events with patients presenting to referral Centers after having received an inadequate surgical treatment. In literature, both the wait-and-see policy and the "aggressive" management with a re-excision have been advocated. The purposes of this study were to analyze the incidence of detectable residual tumor in surgical specimens following a re-excision and to verify the long-term results of patients treated with a re-excision after previous unplanned excision. Methods: We retrospectively evaluated 131 patients affected by localized soft tissue sarcoma (95 high grade; 36 low grade) of the limbs or the superficial trunk treated at our Institution, from 2000 to 2013, with a re-excision after a previous unplanned inadequate excision. Site, size, depth, histotype, grade, adjuvant therapies, time from unplanned surgery to re-excision were recorded and evaluated in association with clinical results. We specifically evaluated the disease-specific survival, local recurrence free survival, distant metastases free survival and the event free survival. Results: Mean follow-up for living patients was 10.9 years (median 11.2 years), with a follow-up ranging from 14 to 227 months. 34% of patients underwent a re-excision within the first 2 months after unplanned surgery, while 66% of patients at more than 2 months. Residual detectable tumor cells were found on histological examination in 54% of re-excisions. A wide margin was obtained in 123 cases, a persisting positive margin in 8 patients. Disease-specific survival was 93.5%, 91.6% and 89.6% at 5, 10 and 15 years for whole series and 90.9%, 88.2% and 85.7% for high grade tumors. Event-free survival in patients affected by high grade tumors rated 75.0% at 5 years, 72.4% at 10 years and 72.4% at 15 years. Local recurrence free survival in high grade tumors was 87.6%, 86.2% and 86.2% at 5, 10 and 15 years. The grade of the tumor (high grade) and the initial dimension of the tumor (≥5 cm) were associated with worst survival. High grade tumor impacted negatively also on local recurrence free survival and event free survival. Instead, the initial size of the tumor significantly affected the event free survival but not the local recurrence free survival. No significant differences of outcome were found analyzing tumor depth, time interval to re-excision, presence of residual tumor or margins. Conclusion: Based on our results and literature findings, we believe that surgeons should offer a re-excision procedure in those patients presenting with an inadequate excision of a high grade soft-tissue tumor, in particular with tumors larger than 5 cm before excision. Indeed, if an adequate second treatment is performed with surgery ± radiotherapy, the long-term results of patients receiving a re-excision after unplanned excision of a high grade soft tissue sarcoma seem to be comparable to the results generally reported for wide primary excisions. More debatable is whether to perform a re-excision or not in patients with low-grade tumors. Perhaps, in this latter group a wait and see policy can eventually be offered as well as in high grade tumors when a re-excision procedure could involve major surgery or significantly affect postoperative function. Highlights: After an unplanned excision, 50% of patients could have residual sarcoma in situ. Initial tumor size and grade are the most important prognostic factors. Long-term follow-up confirm good disease control after re-excision.